Progress towards drug discovery for Friedreich's Ataxia: Identifying synthetic oligonucleotides that more potently activate expression of human frataxin protein. Issue 11 (1st June 2020) - Shen, Xiulong; Wong, Johnathan; Prakash, Thahza P.; Rigo, Frank; Li, Yanjie; Napierala, Marek; Corey, David R.
Graphical abstract: Abstract: Friedreich's Ataxia (FRDA) is an incurable genetic disease caused by an expanded trinucleotide AAG repeat within intronic RNA of the frataxin ( FXN ) gene. We have previously demonstrated that synthetic antisense oligonucleotides or duplex RNAs that are complementary to the expanded repeat can activate expression of FXN and return levels of FXN protein to near normal. The potency of these compounds, however, was too low to encourage vigorous pre-clinical development. We now report testing of "gapmer" oligonucleotides consisting of a central DNA portion flanked by chemically modified RNA that increases binding affinity. We find that gapmer antisense oligonucleotides are several fold more potent activators of FXN expression relative to previously tested compounds. The potency of FXN activation is similar to a potent benchmark gapmer targeting the nuclear noncoding RNA MALAT-1, suggesting that our approach has potential for developing more effective compounds to regulate FXN expression in vivo .